In silico characterisation of antigen receptor binding site structures - Wong, WK (2020)
The adaptive immune system defends the host against the invasion of foreign molecules known as the "antigens". These antigens are recognised by two main types of antigen receptors: T-cell receptors (TCRs) and antibodies. While both proteins share a globally similar β-sandwich architecture and are encoded by similar genetic mechanisms, TCRs are polyspecific and have medium affinity to their peptide antigens, while antibodies are highly specific and have high affinity to their targets. Their different behaviours are thought to be at least partially dictated by their binding site features. In this thesis, we aim to analyse their binding site structures and develop tools that can leverage the greater breadth of binding site diversity unveiled by repertoire sequencing.